2010
DOI: 10.1172/jci42629
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C targets CD8+ dendritic cells to reduce the mortality of endotoxemia in mice

Abstract: Activated protein C (aPC) therapy reduces mortality in adult patients with severe sepsis. In mouse endotoxemia and sepsis models, mortality reduction requires the cell signaling function of aPC, mediated through protease-activated receptor-1 (PAR1) and endothelial protein C receptor (EPCR; also known as Procr). Candidate cellular targets of aPC include vascular endothelial cells and leukocytes. Here, we show that expression of EPCR and PAR1 on hematopoietic cells is required in mice for an aPC variant that med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 73 publications
3
104
0
Order By: Relevance
“…The signaling effects of activated protein C on B cells are still unknown. A recent study discovered that the activation of EPCR on the specific CD8 + subset of spleen dendritic cells is sufficient to suppress immune responses during sepsis and that activated protein C has additional immunosuppressive effects on other dendritic cells in an EPCR-independent manner (38). Our own data are in line with these observations, as recombinant activated protein C reduced the activation of CD4-positive and CD8-positive spleen dendritic cell subsets in MRL-Fas(lpr) mice.…”
Section: Discussionsupporting
confidence: 85%
“…The signaling effects of activated protein C on B cells are still unknown. A recent study discovered that the activation of EPCR on the specific CD8 + subset of spleen dendritic cells is sufficient to suppress immune responses during sepsis and that activated protein C has additional immunosuppressive effects on other dendritic cells in an EPCR-independent manner (38). Our own data are in line with these observations, as recombinant activated protein C reduced the activation of CD4-positive and CD8-positive spleen dendritic cell subsets in MRL-Fas(lpr) mice.…”
Section: Discussionsupporting
confidence: 85%
“…The role of EPCR as a crucial co-receptor for PC activation and aPC-mediated cytoprotective signaling in vascular and immune cells is supported by in vitro and in vivo data (57)(58)(59)(60)(61)(62)(63). However, TF is normally not expressed in the vascular endothelium but co-expressed with EPCR in extravascular cells.…”
Section: Discussionmentioning
confidence: 98%
“…Many mechanisms have been described, but the exact manner in which APC affects sepsis patients is unclear. Therapeutic APC can regulate neutrophil migration and extravasation by direct engagement of 1 and 3 integrins (Elphick, 2009), suppress macrophage activation dependent on integrin CD11b/CD18 (Kerschen, 2010), control maturation and activation of CD8 + DCs dependent on EPCR (Kerschen, 2010), and neutralize late-stage inflammatory mediators by degrading nuclear histones from apoptotic cells . A recent Cochrane review suggested that APC should not be used for treating patients with severe sepsis or septic shock and that APC is associated with a higher risk of bleeding (Marti-Carvajal, 2011).…”
Section: Sepsismentioning
confidence: 99%
“…Bir et al (Bir, 2011) demonstrated that 5A-APC could attenuate lung damage caused by P. aeruginosa in critically ill patients. In addition, 5A-APC inhibits the inflammatory response of conventional dendritic cells independent of EPCR and suppresses IFN-gamma production by natural killer-like dendritic cells (Kerschen, 2010). Recently, an APC variant (APC-L38D/N329Q) was generated with minimal anticoagulant activity, but 5-fold enhanced endothelial barrier protective function and 30-fold improved anti-apoptotic function when compared with wild type APC (Ni, 2011).…”
Section: Engineered Protein C/apcmentioning
confidence: 99%